2012
DOI: 10.1161/circoutcomes.112.965707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extreme Temperatures on Years of Life Lost for Cardiovascular Deaths: A Time Series Study in Brisbane, Australia

Abstract: Background— Extreme temperatures are associated with cardiovascular disease (CVD) deaths. Previous studies have investigated the relative CVD mortality risk of temperature, but this risk is heavily influenced by deaths in frail elderly people. To better estimate the burden of extreme temperatures, we estimated their effects on years of life lost due to CVD. Methods and Results— The data were daily observations on weather and CVD mortality for Brisbane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 41 publications
8
70
1
3
Order By: Relevance
“…In this study, we define heatwave as a sustained period of !2 consecutive days when the temperature ! the 99th percentile of daily mean temperatures (Huang et al, 2012a;Xu et al, 2013;Bobb et al, 2014). The delayed effects of 7 days were also examined using DLNM model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we define heatwave as a sustained period of !2 consecutive days when the temperature ! the 99th percentile of daily mean temperatures (Huang et al, 2012a;Xu et al, 2013;Bobb et al, 2014). The delayed effects of 7 days were also examined using DLNM model.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the best known risk factors for the cause of CVD are related to lifestyle habits such as smoking, alcohol consumption, insufficient physical activity, high blood pressure and cholesterol, and obesity (WHO, 2007), environmental factors such as temperature and air pollution also make a significant contribution to CVD onsets (Gerber et al, 2002). Nevertheless, the evidence on the effects of high temperature to the CVD admissions is less consistent, even though the effect on mortality has been consistently demonstrated in urban locations worldwide (Huang et al, 2012b;Baccini et al, 2008;Basu, 2009;Mcmichael et al, 2008;Yang et al, 2015;Gasparrini et al, 2015;Son et al, 2014;Lubczynska et al, 2015;Guo et al, 2014). For instance, studies have shown that high temperatures are associated with increased hospital visits and admissions for cardio-respiratory diseases both during heatwaves and at other times of the summer in several US cities (Konken et al, 2003;Lin et al, 2009;Shwartz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…людей молодого возраста в отличие от волн холода, во время ко-торых наибольшему риску подвержены пожилые люди [25].…”
Section: терапевтический архив 9 2015unclassified
“…Полученные данные свидетельствуют, что снижение температуры атмосферного воздуха на 1 °С ниже порого-вого уровня ассоциируется с увеличением общего числа смертей на 1,35%, смертности от ССЗ на 1,72%, от респи-раторных заболеваний на 3,3% и от сосудисто-мозговых болезней на 1,25%. Увеличение зимней смертности от ССЗ описано во многих европейских странах [1][2][3][4][5], включая Россию [1,6], США [7], Китай [8], Японию [9], Австралию [10] и Новую Зеландию [11]. Однако причина этого явления неизвестна.…”
Section: терапевтический архив 9 2015unclassified